2019
DOI: 10.1111/1346-8138.14881
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits in adult Japanese patients with atopic dermatitis

Abstract: Dietary habits can modulate the pathogenesis of atopic dermatitis. We evaluated these habits in adult Japanese patients with atopic dermatitis using a validated, brief‐type self‐administered diet history questionnaire and compared the results to those of age‐ and sex‐matched healthy controls. Patients with atopic dermatitis showed higher intakes of carbohydrate and potatoes and lower intakes of alcohol, niacin, meat and oils/fats compared with those of the healthy controls. The results of logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The environmental factors other than smoking may be involved in the pathogenesis of PPP. A dietary habit can be one environmental factor as certain nutrients or foods have disease‐modifying effects on chronic inflammatory diseases, 20,21 especially on psoriasis, a skin disease with enhanced TNF‐α/IL‐23/IL‐17 axis. Saturated fatty acids, red meat, simple sugars, or alcohol exacerbate psoriasis via the activation of TNF‐α/IL‐23/IL‐17 axis, gut dysbiosis or suppression of regulatory T cells (Tregs).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental factors other than smoking may be involved in the pathogenesis of PPP. A dietary habit can be one environmental factor as certain nutrients or foods have disease‐modifying effects on chronic inflammatory diseases, 20,21 especially on psoriasis, a skin disease with enhanced TNF‐α/IL‐23/IL‐17 axis. Saturated fatty acids, red meat, simple sugars, or alcohol exacerbate psoriasis via the activation of TNF‐α/IL‐23/IL‐17 axis, gut dysbiosis or suppression of regulatory T cells (Tregs).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AR ↓ Atopic dermatitis Processed foods and some food additives The occurrence and severity of AD ↑ [253,255] Breastfeeding for the first four months The risk of eczema in the first four years ↓ [257] Feeding infants with intensive eHF in the first 4-6 months, avoiding milk and dairy products Prevent the development of AD [257] Feeding eHF after the sixth month Not suppress the development of AD [258] Monounsaturated fatty acid Allergic sensitization in females, mostly no significant associations for males [258] High n−6/n−3 ratio Moderate to severe AD ↑ [260] The intake of n−6 fatty acids Lower in the severe AD group [261] n−3 PUFA docosahexaenoic acid Beneficial impact on AD [262] Supplementation with polyunsaturated fatty acids of the omega−3…”
Section: Environmental Subs Tan Ce S Affec Ting the Epithelial Barrier Smentioning
confidence: 99%
“…Although some studies have indicated that low n‐3 intake is inversely correlated with AD in women and one randomized control trial noted that AD severity decreases after n‐3 supplementation; another studies have found no association between n‐3 intake and AD, and other clinical studies reported that n‐3 supplementation in adults did not show any benefit over placebo in AD. 259 , 260 , 261 , 262 , 263 , 264 Recently, oxidative stress has been shown to induce AD by increasing the pro‐inflammatory response. 265 Studies conducted on children and adults have found an inverse relationship between serum vitamin C and E levels with AD, and supplementation of vitamin E reduced AD symptoms (Table 4 ).…”
Section: Change In Dietary Habits and Allergic Diseasesmentioning
confidence: 99%
“…The pathogenesis of AD involves a variety of genetic and environmental factors, including diet. 8 Oral intake of certain nutrients could help regulate AD, including vitamin D, vitamin A, -linolenic acid (GLA), eicosapentaenoic acid (EPA), probiotics, or zinc, via the suppression of abnormal immunity, skin barrier impairment, or pruritus ( Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…3). [8][9][10] This article reviews recent studies regarding the regulatory effects of individual nutrients on AD, and possible therapeutic or preventive roles of their oral supplementation in AD.…”
Section: Introductionmentioning
confidence: 99%